Haunt season [videorecording (DVD)] - Elizabeth, Sarah; Scallon, Rob; Bentley, Brent (Darkstar Pictures, 2025)
In the lead-up to Halloween, a young woman joins the cast of a fairground haunted house but gets more than she bargained for when her fellow actors start mysteriously vanishing, one by one. She soon discovers that a masked killer is responsible for these disappearances, murdering his victims in ways that mimic the gruesome deaths of their haunt characters. On Halloween night, the brutality is taken to another level as the killer unleashes a whirlwind of violence on all who dare to enter.